Redes metalorgânicas como catalisadores heterogêneos bifuncionais para reações ácido-base - Cunha, Simonise Figueiredo Amarante (2016)
The metal-organic frameworks (MOFs) are a class of crystalline materials which generally has a central atom (metal ion) coordinated to organic molecules (ligands), combining crystallinity, high porosity and the presence of strong organic metal-ligand interaction. In Catalysis, the MOFs can act as bifunctional catalysts active for both reactions which require basic and acid sites. Zeolitic imidazolate frameworks (ZIFs) is a particularly attractive subfamily of MOFs used for some applications as Catalysis, due to its high chemical and thermal stability, merging the characteristics of zeolites and MOFs. The objectives of this work are the development of bifunctional metal-organic frameworks-based heterogeneous catalysts, for application in reactions that require both acidic and basic sites, comparing them with traditional catalysts (hydrotalcite, aniline, niobium oxide, sulfated zirconia and Amberlyst). Some characterization techniques were performed and the catalysts were evaluated in acid-base type reactions (Knoevenagel condensation and esterification of nbutanol with acetic acid), identifying the parameters that influence the process. Analysis of infrared spectra identified all characteristic bands of the catalysts. The X-ray diffraction showed that, except for niobium oxide (amorphous catalyst), all catalysts have well-defined crystal structure and the diffraction patterns of ZIFs have a single phase and are consistent with the theoretical thereof. Thermogravimetric analysis showed that the ZIF-8, and ZIF-67 are stable up to 520 ° C. The nitrogen physisorption showed that both ZIFs have greater surface area than traditional catalysts and the ZIF-8 showed a value higher than that reported in the literature, moreover, it was observed that both ZIFs have nitrogen adsorption isotherms of type II according to IUPAC characteristic of materials with widely varying pore size. The temperature programmed desorption showed the existence of three basic sites and two acid sites for ZIF-8. The use of catalysts in the Knoevenagel condensation reaction showed that ZIF-67 led to higher conversion, approximately 95% at 24 h. Through the factorial design of condensation reaction using the ZIF-67 as catalyst, it was found that the conversion of the limiting reactant tends to increase significantly with the temperature and catalyst content in the range of conditions studied. The use of catalysts in the esterification reaction of acetic acid with n-butanol showed higher conversions for Amberlyst-15 and conversions below 20% for ZIFs, which may be due to low availability of the acid sites of these catalysts.